THE INFLUENCE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND WORK LIFE BALANCE ON NURSES COMMITMENT IN REGIONAL PUBLIC HOSPITAL Dr. ZUBIR MAHMUD ACEH TIMUR WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Nurul Fajri; Aiyub Yahya; Ibrahim Qamarius; A Hadi Arifin; Mariyudi; Yanita (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This study aims to examine the influence of organizational citizenship behavior and work life balance on nurses commitment with job satisfaction as an intervening variable at RSUD dr. Zubir Mahmud East Aceh. The number of respondents in this study are 115 nurses at RSUD dr. Zubir Mahmud East Aceh. The data analysis method used is Structural Equation Modeling (SEM) by using Amos Software. The results of this study find that organizational citizenship behavior and work life balance directly have positive and significant effect on job satisfaction, then organizational citizenship behavior, work life balance and job satisfaction have positive and significant effect on nurses commitment. The results of the mediation effect test prove that job satisfaction is able to mediate the influence of organizational citizenship behavior and work life balance on nurses commitment fully (full mediation).